The Future of Water in Mining - Treatment of Mine Water for Sustainable Benefit (The Australasian Institute of Mining and Metallurgy, 2008)
We can look at the water treatment and management strategies at some recently commissioned mines and minerals processing sites to see the likely future of water in mining. The future of water in mining will be based on a holistic approach to understanding the site water balance, appropriate treatment, reuse where possible, and environmentally managed discharge where required. This paper describes advanced and innovative water treatment and reuse processes as used by mines and mineral processing operations from around the world. Underground mining can often require dewatering to prevent groundwater seeping into and flooding the mine workings. Mining and processing often accumulates wastewaters in a tailings dam. The mine water can contain contaminants such as dissolved salts, iron, arsenic, manganese, heavy metals and acidic and odorous sulfates. On-site reuse, environmental discharge requirements, as well as community needs for water, drive mine operators to consider the most appropriate water treatment process. Mining water treatment for the future is described using case studies of innovative processes. The case studies include treatment of mine dewatering water for beneficial application from Australian mines, Ballarat Goldfields and Bendigo mining, treatment of produced water from oil and gas projects, and treatment for arsenic removal of tailings water from mining and processing at Goldcorp mines in Canada. Advanced and innovative processes including membrane filtration, reverse osmosis at extreme conditions, advanced biological treatment and water management are all part of these case studies. This paper uses real case studies of advanced and innovative mine water treatment processes to explain and examine the technology and the reasons for designing specific processes. The focus is on innovative processes that may be more widely used in future mining û where the water is used for sustainable environmental discharge or treatment to a quality that can be beneficially used by the mine or the local community.